PELATIHAN OSN BIOLOGI UNTUK SISWA MAS DI MAS MUHAMMAD NADIS BUKITINGGI - Chairul Amri; Helvita Roza; Ratih Komala Dewi; Darmanella Dian Eka Wati; Afrahamiryano Afrahamiryano; Irwan Hanafi (ASOSIASI IDEBAHASA KEPRI, 2026)
Biology OSN training for students at MAS Muhammad Nadis Bukittinggi was conducted to enhance their readiness and competencies for the National Science Olympiad (OSN) in Biology. The program included selection of qualified participants, intensive subject matter delivery, practice problem exercises, and trial examinations (try-outs) to familiarize students with the OSN format. All sessions were facilitated by experienced OSN coaches to ensure quality guidance. An evaluation comparing participants’ pre-test and post-test scores was carried out to measure learning gains. The results showed a significant increase in student abilities, as the average post-test scores were higher than the pre-test scores, indicating the program effectively improved students’ understanding and problem-solving skills. The training had positive impacts, including increased student motivation to learn and improved readiness to participate in OSN selection at the district/city and provincial levels. It also strengthened the role of teachers as mentors in OSN coaching at the school. Supported by active teacher involvement and systematic preparation, the program is expected to continue enhancing student achievement in science competitions at the national level.